The Effectiveness of an Educational Program in Developing Reciprocal Thinking among Intermediate students - Hamad, Ahmed Ibrahim (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of reciprocal thinking among intermediate school students and to develop an educational program designed to enhance this skill. Additionally, the study seeks to evaluate the effectiveness of the educational program in fostering reciprocal thinking among these students. In light of this objective, the researcher formulated the following hypothesis: there is no statistically significant difference between the pre- and post-test scores in the development of reciprocal thinking among middle school students. To assess this hypothesis, the researcher created a reciprocal thinking scale consisting of 40 items, and its psychometric properties were validated. The scale was administered to a sample of 24 students, yielding a reliability coefficient of 0.81, which is considered a good percentage. The research produced the following results: ### Reason: The revised text improves clarity and readability by restructuring sentences, enhancing vocabulary, and correcting grammatical errors. It also maintains the original meaning while ensuring technical accuracy. Preparatory school students often do not engage in interactive thinking. The experimental group demonstrated more interactive thinking than the control group during the educational program lessons.